Investigating Thin-Film Composite Membranes Prepared by Interaction between Trimesoyl Chloride with M-Phenylenediamine and Piperazine on Nylon 66 and Performance in Isopropanol Dehydration - Wan Zulaisa Amira, Wan Jusoh; Sunarti, Abdul Rahman; Abdul Latif, Ahmad; Nadzirah, Mohd Mokhtar; Hasrinah, .Hasbullah (CRC Press, 2022)
FESEM result shows that fabricated TFC membranes employed the dense layer as the active layer. The best water selectivity result from this study was shown by TFC-MPD5 which has ridge-and-valley structure that indicates the best and strong formation (33,150 N m−2) of a complete aromatic PA (in the range of 1,302–1,305 cm−1) on the N66 substrate which is promising for IPA-water separation. Increasing immersion time in amine solution will also increase the crosslinking rate to PA formation that contributed to the increase in thickness of final TFC membranes. In general, the membrane produced by TMC-MPD has better properties and performance than TMC-PIP. TFC membranes prepared by MPD show selectivity of 17.6 and 114.621 for preparing in 3 and 5 minutes in amine solutions, respectively. Meanwhile, TFC prepared by PIP amine solutions shows relatively lower selectivity of 17.6 and 108.5 for TFC-PIP3 and TFC-PIP5, respectively.